Simulating the potential of swarm grids for pre-electrified communities – A case study from Yemen - Martha M. Hoffmann; Dawud Ansari (Renewable and Sustainable Energy Reviews, 2019)
Swarm grids are an emerging approach to electrification in the Global South that interconnects individual household generation and storage to a small electricity network to make full use of existing generation capacities. Using a simulation tool for demand, weather, and power flows, we analyse the potential of an AC swarm grid for a large pre-electrified village in rural Yemen. Service quality and financial indicators are compared to the cases of individual supply and a centralised micro grid. While the swarm grid would improve supply security from the current 12.4% (Tier 2) to 81.7% (Tier 3) at lower levelised costs, it would be inferior to the micro grid in both service (Tier 4) and costs. This is mainly driven by the large pre-installed fossil-fuel generator and storage capacities in our case study. However, this situation may be representative for other relevant locations. Under these conditions, a swarm grid poses the danger of creating (possibly-undesirable) incentives to invest in diesel generators, and it may fail to support prosumerism effectively. Nevertheless, the swarm's evolutionary nature with the possibility for staggered investments (e.g. in smaller yet complementary groups of consumers) poses a central advantage over micro grids in the short-term alleviation of energy poverty.
Keywords: 330; Swarm electrification; Swarm grid; Micro grid; Energy access; Distributed generation; Yemen